Phlebotominae (Diptera: psycodidae) fauna in the Chaco region and Cutaneous Leishmaniasis transmission patterns in Argentina - Salomón, Oscar D. (2008)
In Argentina, the incidence of American Cutaneous Leishmaniasis (ACL) has shown a steady increase over the last few decades. In the Chaco biogeographical region, specifically, several outbreaks of ACL were recently reported in addition to the usual time-space scattering of ACL cases. However, little is known about the sandfly composition in the eastern, humid Chaco (HC) region or the western, dry Chaco (DC) region. Therefore, phlebotomine captures were performed throughout this region and an analysis of the distribution of reported ACL cases was conducted in order to assess the vector diversity in ACL endemic and epidemic scenarios in the Chaco region. The results support the hypothesis of two distinct patterns: (1) the DC, where Lutzomyia migonei was the most prevalent species, had isolated ACL cases and a zoonotic cycle; (2) the HC, where Lutzomyia neivai was the most prevalent species, had an increase in ACL incidence and outbreaks and an anthropozoonotic cycle. The epidemic risk in the Chaco region may be associated with the current climate trends, landscape modification, connection with other ACL foci, and Lu. neivai predominance and abundance. Therefore, changes in sandfly population diversity and density in the Chaco region are an indicator of emergent epidemic risk in sentinel capture sites.